SOCIOSSEMIÓTICA E LITERATURA MARGINAL: COMPLEXOS IDEOLÓGICOS E SISTEMAS LOGONÔMICOS EM CAPÃO PECADO - Vian Jr., Orlando; Balestra, Paulo; Castilho, Nelma Teresinha; Ramos, Aline; Souza, Maria Cristina de (Intercâmbio, 2010)
This paper aims at analysing, based on a previous study (Vian Jr. et alii, 2003), ideological complexes and logonomic systems (Hodge & Kress, 1988), as a means of understanding social-historical elements guiding lexical choices in Capão Pecado, by Ferréz, portraying life in the outskirts of São Paulo.